Acute pancreatitis in SARS-CoV-2 infection: A case report from Tanzania. (October 2022) - Suleiman, Jamil; Sadiq, Abid; Sanga, Evans; Sadiq, Adnan; Urasa, Sarah; Msuya, David; Chugulu, Samwel; Lodhia, Jay
The pandemic caused by the severe acute respiratory syndrome coronavirus 2 has mainly affected the respiratory system but has expanded to other systems, including the gastrointestinal system. We present an 80-year-old man with sharp epigastric pain and vomiting. Laboratory investigations revealed elevated pancreatic enzymes, and contrast-enhanced computed tomography of the abdomen suggested acute pancreatitis. He was undergoing treatment for acute pancreatitis when he developed respiratory compromise, leading to the use of oxygen. Computed tomography of the chest revealed bilateral pleural effusion. However, a positive nasopharyngeal swab suggested severe acute respiratory syndrome coronavirus 2 infection. He was treated for the viral infection with various medications until clinically stable before being self-isolated at home. His follow-up visits revealed a favorable outcome, with progressive resolve occurring 4 weeks after the onset. There is no specific conclusion regarding pancreatic involvement in severe acute respiratory syndrome coronavirus 2 infection. There are several confounding factors in the etiology of acute pancreatitis during concomitant severe acute respiratory syndrome coronavirus 2 infection. However, further research is warranted to evaluate whether pancreatic involvement is one of the clinical presentations or subsequent complications of severe acute respiratory syndrome coronavirus 2 infection.